2015
DOI: 10.1016/j.rinim.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A focused Real Time PCR strategy to determine GILZ expression in mouse tissues

Abstract: Glucocorticoid-Induced Leucine Zipper (GILZ) is a glucocorticoid-inducible gene that mediates glucocorticoid anti-inflammatory effects. GILZ and the isoform L-GILZ are expressed in a variety of cell types, especially of hematopoietic origin, including macrophages, lymphocytes and epithelial cells, and strongly upregulated upon glucocorticoid treatment.A quantitative analysis of GILZ expression in mouse tissues is technically difficult to perform because of the presence of a pseudogene and the high homology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We found that both in vitro and in vivo GILZ expression was enhanced as early as 3 h after GC (DEX) treatment. Up‐regulation of GILZ by DEX was previously also reported in circulating neutrophils in humans and correlated with apoptosis (16); thus, it seems that neutrophils are another myeloid cell type in which GILZ plays an important role (15, 30, 35).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We found that both in vitro and in vivo GILZ expression was enhanced as early as 3 h after GC (DEX) treatment. Up‐regulation of GILZ by DEX was previously also reported in circulating neutrophils in humans and correlated with apoptosis (16); thus, it seems that neutrophils are another myeloid cell type in which GILZ plays an important role (15, 30, 35).…”
Section: Discussionmentioning
confidence: 69%
“…All reagents were purchased from Thermo Fisher Scientific (Waltham, MA, USA). GILZ was amplified as previously described with β‐actin as internal control (30). All experiments were carried out in triplicate, and the ∆∆ C t method was used to determine the expression of target genes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, TSC22D3 or GILZ is one of the most upregulated genes in the microarray dataset that have been previously reported to inhibit migration of leukocytes (33). GILZ gene expression has been shown to be induced by dexamethasone in the whole eye of a mouse (34), and in cultured primary human lens epithelial cells (35), but its expression or its role in the cornea has not been explored. Tumor necrosis factor receptor superfamily, member 11b ( TNFRSF11b ), a promoter of migration (36), is one of the most-repressed genes in this microarray dataset, which was reported to be expressed in corneal stroma (37), however its regulation by glucocorticoids in the cornea has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid-induced leucine zipper is encoded by the TGF-β-stimulated clone (TSC) 22 domain family protein 3 ( Tsc22d3 ) gene located on the X-chromosome and is constitutively expressed in most tissues ( 12 , 16 , 28 ). GILZ is among the earliest and highest GC-induced genes.…”
Section: Gilz’s General Propertiesmentioning
confidence: 99%